2024
DOI: 10.7759/cureus.56543
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and Sedative Properties of Melatonin Premedication in Pediatrics Undergoing Elective Cardiac Catheterization: A Randomized Placebo Study

Hussein A Hussein,
Mohamed Kahloul,
Majid F Alhamaidah
et al.

Abstract: Background: Preoperative anxiety in children has been linked to various postoperative consequences, such as postoperative regressive behavioral issues, extended distress during the recovery period, eating disorders, and bedwetting. The current study aimed to investigate the efficacy of low-dose oral melatonin in alleviating preoperative anxiety among children in the Iraqi population.Study design: A randomized, double-blinded comparative study was undertaken, involving children aged four to 14 years scheduled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Additionally, this dose of sublingual melatonin proved effective in enhancing analgesia and reducing the incidence of spinal-related issues in patients undergoing cesarean section under spinal anesthesia. Our findings regarding the analgesic effect of melatonin align with earlier studies, further supporting the efficacy of melatonin as a premedication agent [3,9,[11][12][13]. The results of studies by Khare et al [14] and Lotfy and Ayaad [15] align with that of the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, this dose of sublingual melatonin proved effective in enhancing analgesia and reducing the incidence of spinal-related issues in patients undergoing cesarean section under spinal anesthesia. Our findings regarding the analgesic effect of melatonin align with earlier studies, further supporting the efficacy of melatonin as a premedication agent [3,9,[11][12][13]. The results of studies by Khare et al [14] and Lotfy and Ayaad [15] align with that of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Administering midazolam or mirtazapine preoperatively for females undergoing cesarean section has been shown to reduce the level of anxiety. However, it's worth noting that both midazolam and mirtazapine may be associated with some unfavorable side effects like an increase in the incidence of postoperative nausea and vomiting (PONV) [2,8,9]. Some previous and recent studies have suggested that the use of melatonin before cesarean surgery, has a role in reducing the oxidative stress in septicemic newborns, enhancing the baby outcomes, and reducing the possibility of oxidative stress incidence or damaging of blood supply of asphyxiated newborns [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Available in various formulations like tablets, capsules, liquids, and gummies, melatonin offers a cost-effective alternative to traditional anesthetics [61,62]. In pediatric patients, melatonin demonstrates efficacy in alleviating preoperative anxiety and inducing significant sedation, rendering it a potential candidate for sedation purposes and facilitating various medical procedures, including venipuncture and mask application during anesthesia induction [63]. However, establishing a consensus on the ideal melatonin dosage for pediatric sedation still needs to be discovered, with reported dosages spanning from 0.3 to 20 mg [63].…”
Section: Cost-effectiveness and Availabilitymentioning
confidence: 99%
“…In pediatric patients, melatonin demonstrates efficacy in alleviating preoperative anxiety and inducing significant sedation, rendering it a potential candidate for sedation purposes and facilitating various medical procedures, including venipuncture and mask application during anesthesia induction [63]. However, establishing a consensus on the ideal melatonin dosage for pediatric sedation still needs to be discovered, with reported dosages spanning from 0.3 to 20 mg [63]. While generally well-tolerated with short-term use, melatonin may elicit diverse albeit infrequent adverse effects, predominantly mild to moderate severity [51].…”
Section: Cost-effectiveness and Availabilitymentioning
confidence: 99%